CRITICAL THINKING PROCESSES OF VOCATIONAL SCHOOL STUDENTS IN SOLVING TRIGONOMETRY PROBLEMS FROM A GENDER PERSPECTIVE - Ratna Febriyanti; Agung Lukito; Susanah Susanah (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
Critical thinking is an essential competency in 21st-century learning and the implementation of the Merdeka Curriculum, particularly for Vocational High School (SMK) students to face the complexities of the workforce. This study aims to describe the critical thinking processes of female and male vocational students in solving trigonometry problems. This study employed a descriptive qualitative approach. The research subjects consisted of one female student and one male student with high mathematical ability. Data were collected through trigonometry problem-solving tasks and task-based interviews. The data were analyzed in-depth using Facione's six critical thinking indicators: interpretation, analysis, inference, evaluation, explanation, and self-regulation. The results indicated distinct characteristics in the thinking processes between the two subjects. The female student demonstrated a systematic and reflective thinking process; she was able to perform accurate interpretation and analysis, utilized evidence-based inference, and showed strong evaluation and self-regulation skills in verifying the solution against problem constraints. In contrast, the male student tended to exhibit an impulsive and intuitive thinking process; he encountered misconceptions during the analysis stage and demonstrated weak evaluation and self-regulation processes, resulting in an illogical final outcome. This study concludes that there are variations in critical thinking process characteristics between female and male vocational students regarding the depth of evaluation and self-regulation when solving trigonometry problems.